Unions as Complex Organizations : Strategy, Structure and the Need for Administrative Innovation - Warner, Malcolm (Relations industrielles / Industrial Relations, 1975)
This paper reports the attempt to extend the theory and method to the organizational structure of occupational interest associations in order to remedy the lacuna in this important area of comparative research namely trade unions and similar bodies.